Job stress, job satisfaction, organizational commitment, and intention to quit among the employees of STIDC in Kuching / Nurnazirah Jamadin … [et al.]. - Jamadin, Nurnazirah; Mohammad, Samsiah; Sharkawi, Zurwina (2010)
Purpose - The purpose of this study is to determine the level of job stressors, job stress, job satisfaction, organizational commitment and intention to quit among of STIDC in Kuching. Sample populations are the staffs of STIDC in Kuching only. The component of job stressors includes role ambiguity, role conflict, workload, and work - family conflict. The components of organizational commitment include affective commitment, continuance commitment, and normative commitment. Design / Methodology! Approach - The study used self administered questionnaires from the Work Place Scale and it is divided into four parts: Job Stressors, Job Stress, Job Satisfaction, and Intention to Quit. Job Stressors were measured four aspect of stress: Role Ambiguity, Role Conflict, Workload, and Work - Family Conflict. Each of the stressors was measured using three items. Organizational Commitment Questionnaires was used to measure affective commitment (8 items), continuance commitment (7 items), and normative commitment (7 items).